Adsorption of Molecular Gases on Silver/Carbon Nanotube Composites at Low Temperatures and Low Pressures. (9th January 2014) - Barberio, M.; Barone, P.; Stranges, F.; Romano, R. A.; Xu, F.; Bonanno, A.
Abstract : We present an experimental study adsorption of molecular gases (N2, H2, O2, CH4, C2 H4, and C2 H6 ) on multiwalled carbon nanotubes (MWCNTs) and MWCNT doped with Ag at low temperatures (35 K) and pressures (10 −6 Torr) using the temperature programmed desorption technique. Our results show that the desorption kinetics is of the first order; furthermore comparative measurements indicate that Ag/MWCNTs have an adsorption capacity higher than that of a pure sample suggesting that these composites are good candidates as gas cryosorbers for applications in cryopumps or sensor of latest generation.